Hubungan Pengajaran Mata Kuliah Ekonomi Islam terhadap Minat Mahasiswa Menabung di Bank Syariah (Universitas Negeri Jakarta, 2017)
This study aims to examine the relationship between teaching of Islamic Economics courses in college and the interest of students to save in Islamic Bank. This is a descriptive-quantitative research by taking a case study of STIE Ahmad Dahlan Jakarta students. The study concluded that there is a significant relationship between the material of Islamic Economics, the intensity of learning , and students' understanding to imcrease the interest of students to save in Islamic Bank.